Adult Mental Health Outpatients Who Have Minor Children: Prevalence of Parents, Referrals of Their Children, and Patient Characteristics - Ruud, Torleif; Maybery, Darryl; Reupert, Andrea; Weimand, Bente; Foster, Kim; Grant, Anne; Skogøy, Bjørg Eva; Ose, Solveig O. (Frontiers in Psychiatry, 2019)
Background A strong connection exists between parental mental illness and mental health risk for their children. It is important to determine the prevalence and characteristics of parents in mental health treatment and identify referral actions for their children. Previous studies indicate that 12-45 percent of adult mental health service patients are parents with minor children. There is a need for studies with larger sample sizes that investigate the prevalence and characteristics of parents, and factors associated with referral actions for their children. Method Data on 23,167 outpatients who are parents with children under 18 years of age were drawn from a national census study across 107 Norwegian adult mental health outpatient clinics in two weeks in April 2013. Clinicians identified various socio-demographic characteristics of patients who were parents and referral actions for their children. Results 8035 (36 percent) of outpatients had children under 18 years. 31 percent were provided with referrals for their children and 58 percent were reported to have children with no need for referral. Three percent were reported to have children with unmet needs who were not referred. There were missing data on children’s needs and referral actions for 8 percent of parents. Patients who care for minor children were more likely to be refugees, and less likely to be single, male, not own a house/apartment, and have a schizophrenia spectrum illness or substance use disorder. Children were more likely to be referred when their parent was single, with no income from paid work, low education, not owning house/apartment, poor family network, long outpatient treatment, and an individual care plan; and less likely for men with a moderate or less severe mental illness. Children were referred to child protection agencies, child and adolescent mental health services and school psychological/pedagogic services. Discussion The prevalence of outpatients with children is similar to other studies. Referrals were made for children of one of three outpatients with minor children. Needs and referrals of children were unknown for one in ten outpatients. Mental health outpatient clinics must improve procedures to identify parenting status and ascertain and act on children’s needs.